Pengembangan Bahan Ajar Digital Gerak Melingkar Berbantuan Scratch Berbasis Science, Technology, Engineering, and Mathematics (UPEJ Unnes Physics Education Journal, 2020)
This research aims to describe the characteristics and to determine the validity of digital teaching materials for circular motion by scratch based on science, technology, engineering, and mathematics (STEM). The research method used is Research and Development (R&D). The subject of this research is a judgement expert (validator). The development of teaching materials is carried out in stages according to the 4D steps (define, design, development, and dissemination). The results showed that (1) the developed teaching materials were presented in the form of e-teaching materials and had STEM content characteristics which included science, technology, engineering, and mathematics. The engineering aspect is represented by a circular motion simulation created using the scratch application. This simulation program aims to visualize the concept of circular motion material that students can work on independently. (2) Digital teaching materials for circular motion by scratch based on were declared valid based on the validity of Aiken’s V.